Impacts of Different Driving Automation Levels on Highway Geometric Design from the Perspective of Trucks - Shuyi Wang; Bin Yu; Yang Ma; Jinzhou Liu; Wen Zhou (Journal of Advanced Transportation)
Truck automation is emerging as an innovative technology with benefits in traffic safety and the economy to revolutionize freight traffic. Despite these benefits, the potential negative or positive effects of different driving automation levels (from no automation to full automation) on highway geometry remained to be determined. In this study, differences related to sight distance characteristics among varied automation levels were firstly discussed and calibrated. Then, seven analysis scenarios of typical levels were proposed. Based on each level with tailored characteristics, the current models of geometric design elements including the required stopping sight distance, horizontal sight line offset, and lengths of vertical curves were revised. Finally, impacts of each level on computed values of those elements were evaluated. Results show that high or full driving automation could substantially lower the requirements of geometric design. Active safety systems have a similar role but with less significant effects. Differently, the driver assistance and partial or conditional automation systems put a higher demand on the road geometric design in terms of driving safety. Outcomes of this study can be used to design real-world geometry of dedicated lanes and provide a methodological basis for the operation of different driving automation features.